2016
DOI: 10.1039/c6cp04761k
|View full text |Cite
|
Sign up to set email alerts
|

Nonresonant electronic transitions induced by vibrational motion in light-induced potentials

Abstract: We find a new mechanism of electronic population inversion using strong femtosecond pulses, where the transfer is mediated by vibrational motion on a light-induced potential. The process can be achieved with a single pulse tuning its frequency to the red of the Franck-Condon window. We show the determinant role that the gradient of the transition dipole moment can play on the dynamics, and extend the method to multiphoton processes with odd number of pulses. As an example, we show how the scheme can be applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In the calculations, to focus on the difference between the RWA and the non-RWA treatments, the effect of the molecular rotational motion is neglected, because the interacting time of the femtosecond laser pulse with the Na 2 molecule is much shorter than the molecular rotational period. This is also consistent with previous theoretical treatments for the interaction of this three-state-model system with the femtosecond laser field (see, e.g., [16,34,42]).…”
Section: T I Sinsupporting
confidence: 92%
See 1 more Smart Citation
“…In the calculations, to focus on the difference between the RWA and the non-RWA treatments, the effect of the molecular rotational motion is neglected, because the interacting time of the femtosecond laser pulse with the Na 2 molecule is much shorter than the molecular rotational period. This is also consistent with previous theoretical treatments for the interaction of this three-state-model system with the femtosecond laser field (see, e.g., [16,34,42]).…”
Section: T I Sinsupporting
confidence: 92%
“…This is also based on the assumption that the transition process mainly occurs around the equilibrium of the Xñ | state where the initial population is distributed. We also note that the R dependence of transition dipole moment may have important influence on the non-resonant electronic transition induced by vibrational motion in light-induced potentials [42], because the shape of the light-induced potential is dependent on the gradient of the transition dipole. In this work, because the calculations are performed under the two-photon resonance condition, the influence of the R dependence of the transition dipole moment is not expected to be strong.…”
Section: T I Sinmentioning
confidence: 91%
“…Equation can be numerically solved by using the split‐operator short‐time propagation method, with the Hamiltonian and the wavefunction expanded on an evenly separated grid (see, for example, Refs. ). The initial wavefunction is set to be the v = 8 vibrational level which can be obtained by using the Fourier grid Hamiltonian (FGH) method …”
Section: Theorymentioning
confidence: 97%
“…In addition, because of intramolecular vibrational redistribution (IVR) and conical intersections (or other nonadiabatic couplings) one typically needs to move the population rapidly through the transition state, which favors doing it in the absence of a barrier in the excited state. Using strong fields to drive the electronic absorption leads naturally to study the effect of vibrational motion (or vibrational coherence) to enhance such absorption. Recent results in two-photon processes (such as a pump-dump mechanism) have shown that the optimization of the initial wave packet is less important when the pulses are time-delayed . In this work we investigate its role in isomerization reactions, with the wider goal of finding new mechanisms to enhance the yield and especially accelerate the rate of the reaction.…”
Section: Introductionmentioning
confidence: 99%